2007
DOI: 10.1163/156856207781494449
|View full text |Cite
|
Sign up to set email alerts
|

Directed growth and differentiation of stem cells towards neural cell fates using soluble and surface-mediated cues

Abstract: Stem and progenitor cells are helping researchers understand the complex process of mammalian development and also show great promise in treating diseases that are unresponsive to standard therapies. The potential for embryonic stem cells to differentiate into any cell in the body is their great benefit but avoiding co-culture with animal cells and efficiently narrowing cell fate to a single cell type remains challenging. Adult progenitor cells have a more restricted cell fate, but have the potential for use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Studies have shown that a stiffer matrix can induce tensional forces, causing the cell–matrix adhesion proteins to trigger a mechanotransductive pathway. 6 , 9 , 74 , 75 Thus, we infer that the effect from the drop of β-1 integrin expression, associated with the reduced number of collagen molecules in a composite fiber, is counterbalanced to some extent by the effect of the extensive cell polarization and increased fiber stiffness; however, a further decrease of collagen percentage in composite fibers (CS30 and CS60) did not lead to further augmentation of hdpPSC differentiation despite the continuous increase in matrix stiffness. These results suggest that a fine balance between the physical and biochemical cues is imperative to achieve rapid and effective neural differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown that a stiffer matrix can induce tensional forces, causing the cell–matrix adhesion proteins to trigger a mechanotransductive pathway. 6 , 9 , 74 , 75 Thus, we infer that the effect from the drop of β-1 integrin expression, associated with the reduced number of collagen molecules in a composite fiber, is counterbalanced to some extent by the effect of the extensive cell polarization and increased fiber stiffness; however, a further decrease of collagen percentage in composite fibers (CS30 and CS60) did not lead to further augmentation of hdpPSC differentiation despite the continuous increase in matrix stiffness. These results suggest that a fine balance between the physical and biochemical cues is imperative to achieve rapid and effective neural differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…12,4348 Various methods including dip pen nanolithography, 49 UV lithography 50 and electro-spun nanofibers 50,51 have been utilized to align cells in microscale. In this study, we used aligned CNTs to guide the direction of focal adhesions and polarization of cells.…”
Section: Resultsmentioning
confidence: 99%
“…3,6,7 These forces are mediated by transmembrane adhesion proteins and can therefore affect the expression of signaling proteins. 1214 Integrin-linked kinase activation has been reported to increase cytoplasmic levels of β -catenin, which positively affects the Wnt- β catenin signaling pathway. However, the role of individual physical forces in control of cell polarity and orientation remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, for in vivo implantation studies, biodegradable polymers would in most cases be more desirable. A number of biodegradable polymers, including poly‐(D,L‐lactic acid) (PDLA), poly‐(lactic‐coglycolic acid) (PLGA), and poly‐(L‐lactic acid) (PLLA), have been used as biological scaffolds (Boote Jones and Mallapragada, 2007). These polymers, as well as others, which could be micropatterned similarly to the polystrene used in this study, may be useful as cellular delivery scaffolds for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of the pattern are 16 × 13 × 4 μm (groove width, mesa width, mesa height). Previous studies have demonstrated that the vast majority of Schwann cells, astrocytes, and adult rat hippocampal progenitor cells morphologically align in the direction of the grooves on micropattern substrates of these dimensions (Recknor et al, 2004, 2005, 2006; Rutkowski et al, 2004; Boote Jones and Mallapragada, 2007). Polystyrene beads (MW 125,000–250,000; Polysciences, Warrington, PA) were diluted in toluene at 8% weight/volume, which was cast on silicon wafers containing micropatterning and was cast until dried.…”
Section: Methodsmentioning
confidence: 99%